A note on circular neighbor balanced designs. Issue 10 (26th November 2018) - Jaggi, Seema; Pateria, Dinesh Kumar; Varghese, Cini; Varghese, Eldho; Bhowmik, Arpan
ABSTRACT: This paper describes some methods of constructing circular neighbor balanced and circular partially neighbor balanced block designs for estimation of direct and neighbor effects of the treatments. A class of circular neighbor balanced block designs with unequal block sizes is also proposed.